Spatial discrimination deficits as a function of mnemonic interference in aged adults with and without memory impairment. Issue 3 (12th November 2013) - Reagh, Zachariah M.; Roberts, Jared M.; Ly, Maria; DiProspero, Natalie; Murray, Elizabeth; Yassa, Michael A.
ABSTRACT It is well established that aging is associated with declines in episodic memory. In recent years, an emphasis has emerged on the development of behavioral tasks and the identification of biomarkers that are predictive of cognitive decline in healthy as well as pathological aging. Here, we describe a memory task designed to assess the accuracy of discrimination ability for the locations of objects. Object locations were initially encoded incidentally, and appeared in a single space against a 5 × 7 grid. During retrieval, subjects viewed repeated object‐location pairings, displacements of 1, 2, 3, or 4 grid spaces, and maximal corner‐to‐opposite‐corner displacements. Subjects were tasked with judging objects in this second viewing as having retained their original location, or having moved. Performance on a task such as this is thought to rely on the capacity of the individual to perform hippocampus‐mediated pattern separation. We report a performance deficit associated with a physically healthy aged group compared to young adults specific to trials with low mnemonic interference. Additionally, for aged adults, performance on the task was correlated with performance on the delayed recall portion of the Rey Auditory Verbal Learning Test (RAVLT), a neuropsychological test sensitive to hippocampal dysfunction. In line with prior work, dividing the aged group into unimpaired and impaired subgroups based on RAVLT Delayed Recall scores yielded clearly distinguishable patterns of performance, with the former subgroup performing comparably to young adults, and the latter subgroup showing generally impaired memory performance even with minimal interference. This study builds on existing tasks used in the field, and contributes a novel paradigm for differentiation of healthy from possible pathological aging, and may thus provide an avenue for early detection of age‐related cognitive decline. © 2013 Wiley Periodicals, Inc.